Effects of commercial bacterial inoculants on fermentation and nutritive quality of wheat and annual legume mixed silages (Bangladesh Journal of Botany, 2023)
In the present study fermentation quality, microbial populations and nutritive value of wheat and some cool season annual legume (forage pea, grass pea and vetch) mixed silages (25:75, 50:50 and 75:25) using various commercial bacterial inoculants (Pioneer 1188, Pioneer 11A44 and Pioneer 11CFT) were determined. Wheat and legume species were sown in separate plots and these plants were harvested when wheat reached the dough stage about 180 days after plant emergence. The present study was conducted in a factorial (3 legume species×3 inoculants×5 mixtures) arrangement design. Results showed that effects of legume species on ADF, crude ash, pH, lactic acid bacteria, enterobacteria, yeast and mold, lactic acid, acetic acid, propionic acid, butyric acid and ammonia nitrogen were significant (P < 0.05). Crude protein, silage fermentation features and microbial populations were affected (P